Equine Penile Squamous Cell Carcinomas as a Model for Human Disease: A Preliminary Investigation on Tumor Immune Microenvironment - Ilaria Porcellato; Samanta Mecocci; Luca Mechelli; Katia Cappelli; Chiara Brachelente; Marco Pepe; Margherita Orlandi; Rodolfo Gialletti; Benedetta Passeri; Angelo Ferrari; Paola Modesto; Alessandro Ghelardi; et al. (Cells, 2020)
Penile squamous cell carcinomas (SCCs) are common tumors in older horses, with poor prognosis mostly due to local invasion and recurrence. These tumors are thought to be mainly caused by Equus caballus papillomavirus type 2 (EcPV-2). The aim of this study is to characterize the tumor immune environment (TIME) in equine penile tumors. Equine penile epithelial tumors (17 epSCCs; 2 carcinomas in situ, CIS; 1 papilloma, P) were retrospectively selected; immune infiltrate was assessed by histology and immunohistochemistry; RT-qPCR tested the expression of selected chemokines and EcPV-2 DNA and RNA. The results confirmed EcPV-2-L1 DNA in 18/20 (90%) samples. L1 expression was instead retrieved in 13/20 cases (65%). The samples showed an increased infiltration of CD3+lymphocytes, macrophages (MAC387; IBA1), plasma cells (MUM1), and FoxP3+lymphocytes in the intra/peritumoral stroma when compared to extratumoral tissues (p < 0.05). Only MAC387+neutrophils were increased in EcPV-2high viral load samples (p < 0.05). IL12/p35 was differentially expressed in EcPVhigh and EcPVlow groups (p = 0.007). A significant decrease of IFNG and IL2 expression was highlighted in TGFB1-positive samples (p < 0.05). IBA1 and CD20 were intratumorally increased in cases where IL-10 was expressed (p < 0.005). EpSCCs may represent a good spontaneous model for the human counterpart. Further prospective studies are needed in order to confirm these preliminary results.